Functional MRI activation of the nucleus tractus solitarius after taste stimuli at ultra-high field: a proof-of-concept single-subject study - Canna, Antonietta; Cantone, Elena; Roefs, Anne; Franssen, Sieske; Prinster, Anna; Formisano, Elia; Di Salle, Francesco; Esposito, Fabrizio (Frontiers in Nutrition, 2023)
Using ultra-high field (7 Tesla) functional MRI (fMRI), we conducted the first in-vivo functional neuroimaging study of the normal human brainstem specifically designed to examine neural signals in the Nucleus Tractus Solitarius (NTS) in response to all basic taste stimuli. NTS represents the first relay station along the mammalian taste processing pathway which originates at the taste buds in the oral cavity and passes through the thalamus before reaching the primary taste cortex in the brain. In our proof-of-concept study, we acquired data from one adult volunteer using fMRI at 1.2 mm isotropic resolution and performed a univariate general linear model analysis. During fMRI acquisition, three shuffled injections of sweet, bitter, salty, sour, and umami solutions were administered following an event-related design. We observed a statistically significant blood oxygen level-dependent (BOLD) response in the anatomically predicted location of the NTS for all five basic tastes. The results of this study appear statistically robust, even though they were obtained from a single volunteer. The information derived from a similar experimental strategy may inspire novel research aimed at clarifying important details of central nervous system involvement in eating disorders, at designing and monitoring tailored therapeutic strategies.